2011
DOI: 10.1111/j.1442-2042.2011.02779.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyaluronic acid on urine nerve growth factor in cyclophosphamide‐induced cystitis

Abstract: Objectives: To investigate how hyaluronic acid (HA) affects nerve growth factor (NGF) production and bladder overactivity in a cyclophosphamide (CYP)-induced cystitis rat model. Methods: Female Sprague-Dawley rats received three intermittent intraperitoneal injections of CYP (75 mg/kg) or saline. Before or after CYP injection, HA was given intravesically and urine NGF was checked with creatinine correction. Bladder function was evaluated by cystometrograms under Zoletil anesthesia. Furthermore, the effect of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Systemic treatment of rats with this experimental cystitis model, with an NGF sequestering molecule, has been shown to reduce the bladder overactivity that develops . Another study that reported a significant increase in NGF production, after cyclophosphamide ‐induced cystitis in female rats, showed this was also associated with a decreased intercontraction interval . Once hyaluronic acid was administered intravesically, this significantly reduced the urinary NGF levels and increased the intercontraction interval.…”
Section: Tissue Ngf Levels: Animal and Human Studiesmentioning
confidence: 90%
“…Systemic treatment of rats with this experimental cystitis model, with an NGF sequestering molecule, has been shown to reduce the bladder overactivity that develops . Another study that reported a significant increase in NGF production, after cyclophosphamide ‐induced cystitis in female rats, showed this was also associated with a decreased intercontraction interval . Once hyaluronic acid was administered intravesically, this significantly reduced the urinary NGF levels and increased the intercontraction interval.…”
Section: Tissue Ngf Levels: Animal and Human Studiesmentioning
confidence: 90%
“…Cystometry was carried out as described previously . The rats were prohibited from drinking water 12 h before CMG, and their bladders were emptied before CMG.…”
Section: Methodsmentioning
confidence: 99%
“…Important components of the GAG layer include chondroitin sulfate, hyaluronic acid, heparin sulfate, dermatan sulfate, and keratin sulfate (135), and some agents with GAG-like properties, such as sodium hyaluronate, heparin, and pentosan polysulfate, have been admin-istered intravesically to IC/BPS patients with variable results (87,208,233). In rats, hyaluronic acid was shown to reduce NGF production and bladder overactivity in a cyclophosphamide (CYP)-induced cystitis rat model (133).…”
Section: Treatments Targeting the Mucosamentioning
confidence: 99%